Introduction: AI and the Future of Literary Studies. - Conti, Christopher (Australian Literary Studies)
The article focuses on the impact of artificial intelligence on humanities education and the future of literary studies. It examines how the push for AI literacy and vocationally oriented programs in universities, driven by fears of automation and job scarcity, risks undermining critical thinking and academic literacy, while highlighting the tension between market-driven reforms and the enduring value of humanistic learning.